Obama and the macroeconomy estimating social preferences between unemployment and inflation - Soeren Enkelmann (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2013)
This paper investigates social preferences towards unemployment and inflation in the United States. Estimating a popularity function with monthly data for the recent Obama administration, we find that U.S. voters react strongly to both unemployment and inflation. However, reducing unemployment is more important to society as voters would trade off 1 point of unemployment against 2.5 points of inflation. One point of unemployment costs the president about 4 points, one point inflation costs him 1.5 point. Moreover, we provide evidence that macroeconomic preferences are not stable over time. Finally, we show that public preferences towards unemployment and inflation are not homogeneous a ross different groups in society. The poor and low-educated, for example, react more strongly to changes in the unemployment rate than other groups.
Keywords: D72; H11; 330; social preference function; popularity function; unemployment; inflation; Obama